A proposed new psychological model for judgement and decision-making: Integrating the tri-partite model with hemispheric difference. Issue 4 (5th June 2017) - Wray, Christopher
Abstract : Purpose: The purpose of this paper is to consider the implications for leadership development of a proposed new psychological model based on the integration of two distinct fields of research in cognitive science and neuroscience, namely, judgement and decision-making in the heuristics and biases tradition, and in particular the dual-process theory of cognition and its development into a tri-partite model; and the differences between the distinct modes of attention supported by left and right cerebral hemispheres. Design/methodology/approach: The distinct fields of research are critically reviewed, the proposed new integrated conceptual framework is presented and compared with other relevant theory, and finally the implications for practice and the connection with contemporary leadership development theory are explored. Findings: It is suggested that decision-makers' performance in volatile or complex environments could be enhanced through the appropriate engagement of each among the expanded set of cognitive faculties identified in the proposed model, and that a decision-making methodology incorporating prompts to engage each of these aspects of cognition could be adopted by individuals or embedded in organisational processes. Research limitations/implications: Potential connections for future research are suggested between the proposed new conceptual framework and existing theories concerning shared leadership in teams and reframing processes in a relational leadership context, and more comprehensive psychological theories of leadership incorporating relevant personality traits. Testable claims for future research are proposed, as the model is yet to be validated empirically. Originality/value: This paper proposes a novel, integrated psychological model with potential relevance both as a conceptual framework for future research in contemporary leadership theory and as the basis for a decision-making methodology with practical application in leadership development.